Optical properties and structure particularities of LiNbO3 crystals grown from a boron-doped melt - Sidorov, Nikolay V.; Palatnikov, Mikhail N.; Teplyakova, Natalya А.; Titov, R. A.; Bormanis, Karlis Ya (Taylor and Francis Ltd., 2019)
A series of LiNbO3:B crystals was grown from the melt doped by boron. It is shown that LiNbO3:B crystals possess an increased resistance to optical damage. We have found changes according to Raman spectra confirming the ordering of Li+, Nb5+ cations and vacancies along the polar axis. The chemical interactions were studied in the system Li2O–B2O3–Nb2O5. Boron cations are unable to incorporate into a cation sublattice of LiNbO3, but they change the physic-chemical structure of a melt. It contributes to an increased structure and optical uniformity of LiNbO3:B.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; boron doping; Lithium niobate single crystal; pattern of photoinduced light scattering; photorefractive effect; Raman spectroscopy